INCIDENCE OF ERYTHROCYTE GLUCOSE-6-PHOSPHATE- DEHYDROGENASE DEFICIENCY - Sh. Rahbar; M. Mir Ahmadian; P. Bahadory; F. Berelian (Tehran University of Medical Sciences, 1974)
In a survey carried out to establish the incidence of erythrocyte glucose 6-phosphate-dehydrogenase deficiency, 738 professional blood donors of Tehran were examined. The fluorescent spot technique was used for screening and qualitative determination of G-6-PD in erythrocytes. This technique was compared with other methods of G-6-PD enzyme assay and proved to be very reliable. Qualitative enzyme estimation was carried out with spectrophotometer methods. A total of 738 specimens tested and some degree of enzyme deficiencies were detected. In 20 specimens there was a complete enzyme deficiency and in 5 cases the enzyme activity was between 15 to 50 percent of normal subject. The data suggests, the blood bank should be warned of transfusion of enzyme deficient bloods to the patients with fauvism.